Choroidal evaluation of FTLD-Tau and biomarker-determined Alzheimer’s disease - Benjamin J. Kim; Tomas S. Aleman; Katheryn A. Q. Cousins; Ebenezer Daniel; Eli Smith; Emma Iacobucci; Anton Kolomeyer; Christopher K. Hwang; Corey T. McMillan; Vivianna M. Van Deerlin; Jeffrey S. Phillips; Yinxi Yu; et al. (Scientific Reports)
Abstract Frontotemporal lobar degeneration with tauopathy (FTLD-Tau) can present clinically similar to Alzheimer’s disease but lacks a biomarker. Alzheimer’s disease has been associated with choroidal thinning compared to controls. We compared the choroid of 25 probable FTLD-Tau (pFTLD-Tau) patients (42 eyes), 26 biomarker-determined probable Alzheimer’s disease neuropathologic change (pADNC) patients (49 eyes), and 53 normal controls (80 eyes). Cerebrospinal fluid biomarkers determined presence of ADNC. All pFTLD-Tau patients had a syndrome highly associated with FTLD-Tau. Optical coherence tomography was performed with masked manual choroidal thickness (CT) measurements. With Image J, binarized images determined the choroidal vascularity index (CVI). Linear regression with generalized estimating equations to account for inter-eye correlation was performed. For pFTLD-Tau, pADNC, and controls, the subfoveal CT was 308.9, 286.0, and 301.5 μm, and CVI was 0.72, 0.72, and 0.73, respectively (all p > 0.05 for each group comparison). Adjusting for demographics, the CT and CVI were not significantly different between groups, including 13 CT measurement locations (all p > 0.05). Among pADNC patients, an exploratory analysis found a correlation between CVI and disease duration (Pearson r = 0.32, p = 0.04). We found no significant difference of CT or CVI between pFTLD-Tau, pADNC, and controls. Additional studies are warranted to evaluate how CVI relates to ADNC.